1991
DOI: 10.1093/nar/19.8.1779
|View full text |Cite
|
Sign up to set email alerts
|

A eukaryotic genome of 660 kb: electrophoretic karyotype of nucleomorph and cell nucleus of the cryptomonad alga,Pyrenomonas salina

Abstract: Cryptomonads are unicellular algae with chloroplasts surrounded by four membranes. Between the inner and the outer pairs of membranes is a narrow plasmatic compartment which contains a nucleus-like organelle called the nucleomorph. Using pulsed field gel electrophoresis it is shown that the nucleomorph of the cryptomonad Pyrenomonas salina contains three linear chromosomes of 195 kb, 225 kb and 240 kb all of which encode rRNAs. Thus, this vestigial nucleus has a haploid genome size of 660 kb, harboring the sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…We have therefore sequenced both the nuclear and the nucleomorph 18S rRNA genes of six diverse cryptomonads in order to see whether or not the trees derived from the two separate genomes are congruent. Together with previous data from five other cryptomonads (Douglas et al, 1991;Eschbach et al, 1991a;Maier el al., 1991;Cavalier-Smith et al, 1994) this enables us to clarify several important aspects of cryptomonad phylogeny. We particularly wished to examine two key questions.…”
Section: Introductionsupporting
confidence: 77%
“…We have therefore sequenced both the nuclear and the nucleomorph 18S rRNA genes of six diverse cryptomonads in order to see whether or not the trees derived from the two separate genomes are congruent. Together with previous data from five other cryptomonads (Douglas et al, 1991;Eschbach et al, 1991a;Maier el al., 1991;Cavalier-Smith et al, 1994) this enables us to clarify several important aspects of cryptomonad phylogeny. We particularly wished to examine two key questions.…”
Section: Introductionsupporting
confidence: 77%
“…2 (CCMP 242)] were cultured as described (15), and total DNA was isolated as described (19). Nuclei were isolated as described (12). Universal cytoplasmic-type srRNA gene primers (5'-TACCTGGTGGATCCT-GCCAG-3' and 5'-TGATCCTTCTGCAGGTTCACCTAC-3') were used to amplify srRNA genes by PCR (10).…”
Section: Methodsmentioning
confidence: 99%
“…Flagellate cells of Chlorarachnion sp. 1 were embedded in plugs of low-gellingtemperature agarose at 1.4 x 108 cells per ml and then digested as described (12). Chromosomal DNAs were electrophoresed in 1% agarose (SeaKem LE, FMC) in a CHEF DRII apparatus (Bio-Rad) at 170 V with a 20-sec pulse for 30 h. DNA was transferred to ZetaProbe nylon membrane (Bio-Rad) as recommended by the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
“…Far and away the most extreme examples of eukaryotic genome reduction are the ''nucleomorph'' genomes of cryptophytes and chlorarachniophytes. Nucleomorphs are the relic nuclei of algal endosymbionts that became permanent inhabitants of nonphotosynthetic eukaryotic host cells (3)(4)(5). Through the combined effects of genome compaction and intracellular gene transfer, the nucleomorph genomes of cryptophytes and chlorarachniophytes have shrunk to a fraction of the size of the algal nuclear genomes from which they are derived and, thus, represent a fascinating system for studying the process of genome evolution.…”
mentioning
confidence: 99%
“…Preliminary karyotype diversity studies have revealed considerable size variation, with estimated nucleomorph genome sizes ranging from Ϸ450 to 845 kbp in cryptophytes and Ϸ330-610 kbp in chlorarachniophytes (4,(10)(11)(12)(13)(14). The presence of three chromosomes is thus far a universal feature of nucleomorph genomes (3,12,14), as is the existence of subtelomeric rDNA repeats.…”
mentioning
confidence: 99%